COMPARATIVE STUDY REGARDING THE FLUORESCENCE OF DIFFERENT TYPES OF COMPOSITE RESINS - Simona Stoleriu; Gianina Iovan; Angela Ghiorghe; Galina Pancu; Claudiu Topoliceanu; Irina Nica; Sorin Andrian (Romanian Society of Oral Rehabilitation, 2015)
The aim of study was to compare the level of fluorescence emission of two types of composite resins customary used in dental practice. Material and method. Two composite resins were used in this study: Herculite XRV (Kerr Company) and Z250 (3M ESPE). The enamel was restored with shades A3 for both composite resins, while dentine was restored with A3 for Herculite and universal dentine shade for Z250. From each material were performed 6 samples having 50 mm in lenght, 5 mm in width and 1mm in height. The samples were obtained by materials photopolymerisation between two glass plates with a LED lamp (LED B, Guilin Woodpwcker Medical Instrument Co., Ltd, China) for 40 seconds. The fluorescence emission of the composite resins was assesed by spectrometry (using spectrometer device LS 55, Perkin Elmer Inc, USA). The samples were excited using an UV fascicle with wavelength spectrum between 330-630 nm. The spectrum of emission was recorded using software FL Win Lab. Results. Considering this spectrum, the fluorescence emission for Herculite XRV dentine had the peak around 452 nm. For Herculite XRV enamel, considering the same spectrum of wavelenght, the fluorescence emission had the peak around 443,5 nm. The fluorescence emission of Z 250 dentine recorded the peak for wavelenght spectrum of UV fascicle between 330 şi 630 nm. Conclusions. For both tested materials, the fluorescence emission of dentine shades was higher comparing with enamel shades. The highest values of fluorescence emission were recorded for highest values of wavelengths, for both composite resins included in study